“QUEM SOUL EU”: a transitoriedade na performance de Linn da Quebrada por um viés interseccional - Cordova, Jonara (Universidade do Vale do Rio dos Sinos, 2022)
The objective of this dissertation is to raise some reflections on the relationship between artistic performance and gender performativity in artivist production, from an intersectional point of view. Using as a clipping the transition between the albums Pajubá (2017) and Trava Línguas (2021), by multi-artist Linn da Quebrada, I investigate the main themes triggered by her in her performances in media appearances. I also question how these themes relate to her experience as a transvestite, black and peripheral, considering the crossings of these intersecting avenues of oppression. To carry out the investigation, I used as methodological contributions the Grounded Theory and the Intersectional Roulette, articulated, making adaptations to account for the phenomenon studied. From the coding of the collected data, it was possible to identify the four categories that make up the transition process between the two discs: Self-Investigation, Death, Invention and Rebirth. The intersection between the categories forms the central category Encruzilhada, in which Linn da Quebrada is at the center. The results culminated in reflections about the constant transience and the construction of other imaginaries for abject bodies, from tactical actions of resistance performed in music and art as a whole.
Keywords: Performance; Performatividade de gênero; Interseccionalidade; Artivismo; Linn da Quebrada; Gender performativity; Intersectionality; Artivism; ACCNPQ::Ciências Sociais Aplicadas::Comunicação